2015
DOI: 10.1186/s13063-015-0758-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a hospital-based day-structuring exercise programme on exacerbated behavioural and psychological symptoms in dementia - the exercise carrousel: study protocol for a randomised controlled trial

Abstract: BackgroundConceptual reviews and observational studies describe a link between physical inactivity and behavioural disturbances in people with dementia. Consequently, treatment of these symptoms requires physical activation and pharmacological or physical immobilization should be avoided. The few trials that have been conducted in inpatient dementia care to investigate the effects of exercise on behavioural and psychological symptoms revealed inconsistent results. Due to a lack of evidence, there is a paucity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 51 publications
0
19
0
3
Order By: Relevance
“…Pre and post assessment was conducted 3 days before and after the intervention respectively. For further details, refer to the study protocol published previously [ 13 ]. The RCT has been registered in the German Clinical Trial Register (DRKS00006740) and has been approved by the local ethics committee.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pre and post assessment was conducted 3 days before and after the intervention respectively. For further details, refer to the study protocol published previously [ 13 ]. The RCT has been registered in the German Clinical Trial Register (DRKS00006740) and has been approved by the local ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…The following inclusion criteria were applied: diagnosis of dementia according to ICD-10 [ 14 ]; a minimum length of stay of 1 week before enrollment into the study in order to help patients become familiarized with the ward setting and to exclude delirium; clinical exclusion of delirium based on the validated German version of the Confusion Assessment Method [ 15 , 16 ]; ability to perform the Timed Up and Go Test [ 17 ]; and written informed consent from the patient’s legal guardian as well as from the patient, if possible. According to the sample size calculation published in the study protocol [ 13 ], each group should include 53 patients respectively. Therefore, an enrollment of 130 patients was planned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent clinical trial showed no significant effect of donepezil treatment on BDNF levels (166), while a 2009 clinical trial have indicated an increase in BDNF levels in lithium-treated patients with early AD (167). BDNF levels have been analyzed as a biomarker in other clinical trials conducted on AD treatment, especially in trials on the effect of physical activity and exercise on AD (168)(169)(170). Beneficial effect of BDNF in several mouse models of AD has also been reported.…”
Section: Neurotrophic and Hematopoietic Growth Factors Brain-derived mentioning
confidence: 99%